Enrichment of Material and Training for Solving Chemistry Olympiad Questions for Teachers at SMAN 1 Ampek Angkek - Desy Kurniawati; Eka Yusmita; Edi Nasra (Fakultas MIPA Universitas Negeri Padang, 2021)
One indicator of the success learning process in schools is the success of students in academic competitions such as the National Science Olympiad (OSN). This training aims to improve the ability of Chemistry MGMP teachers in Agam district in understanding the material and mastering problem-solving strategies in solving high school level Chemistry OSN questions. In addition, this training is expected to help teachers prepare their students to face OSN Chemistry. The number of teachers who took part in the chemistry olympiad interview and training activity were 18 participants who were chemistry teachers throughout Agam district. The stages in this training consist of (1) literature study on inorganic, analytical, organic, and physical chemistry materials, (2) preparation of training materials in the form of Chemistry Olympiad modules, (3) training implementation which consists of presenting material and mentoring to participants. In solving practice questions, (4) implementing teacher evaluation activities through pre and post test activities on chemistry olympiad questions. Based on the evaluation of the teacher's pre and post test scores, it was found that the posttest results increased with an average value of 47.9 while the pretest score had an average value of 34.72.